Inter-lingual Homophony: Neige as a Demonstrative/Filler in Mandarin Chinese - Wang, Aiqing (Studia Orientalia Electronica, 2021)
The demonstrative/filler neige in Mandarin Chinese is potentially contentious outside that language,as it bears resemblance in terms of pronunciation with a racial slur in English. Nonetheless, neigedoes not possess any racist connotation in Mandarin Chinese, and its analysis needs to take intoconsideration historical and contextual information. The form neige is a colloquialism of its formalequivalent nage, which has functioned as a demonstrative determiner/pronoun or a discoursemarker in verbal communication since ancient periods. The derivation of nei from na is realisedvia suppression of the demonstrative with the numeral yi ‘one’, and this phenomenon occurredeven before Mandarin was invented as a national lingua franca. Differently from languages suchas English in which the number of homophones is limited, Chinese contains an enormous amountof syllables with myriads of homophones, owing to the fact that Chinese is a tone language thatdepends on tone implications to differentiate meanings and syllables/words are hence predominantlymono- or bi-morphemic. As a consequence, homophones pertaining to Chinese aboundboth language-internally and cross-linguistically. Among the repercussions of homophony are theliterary inquisitions during the Qing era that sabotaged freedom of creation. Therefore, the interpretationand comprehension of neige need to be objective and impartial.